DILEMATIS UMKM DI ERA DIGITAL - Saprianto, Febi (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
UMKM is a pillar for most Indonesian people. This is proof, the state must be present, by providing facilities, such as guaranteeing economic stability, stable prices, ease of capital, partnerships, etc. Especially in the current digital era. MSMEs must take a role, by utilizing existing resources, and optimizing technology. this research is present as a form of proof of the role of MSMEs for the welfare of society. on the other hand, see what things are becoming a nuisance to MSMEs. To test the problem formulation, a qualitative approach is used. Where the research emphasis is on what happens to the SMEs, especially in the South Tangerang region. Observation was chosen as a way to obtain convincing data. Research results show, that MSMEs have not been able to exploit the digital era, plus the role of the state has not been felt